An evaluation of structural markers in some Northern Sotho/English bilingual dictionaries :a lexicographic perspective - Letsoalo, Alydia Modjadji (My University, 2012)
Structural markers, front matter, contextual guidance and cross-referencing are some of the important features of bilingual dictionaries which are often taken for granted. This study evaluates the presentation of structural markers in some Northern Sotho/English Bilingual dictionaries, with special reference to Pharos: Popular Northern Sotho Dictionary and Sesotho sa Leboa/English Pukuntšu Dictionary. The study further evaluates the use of the front matter, contextual guidance and cross-referencing in bilingual dictionaries. The study has established that bilingual dictionaries can become user-friendly if they identify and use appropriate strategies, as this leads to communicative success. By contrast, the incorrect application of a comma or a semicolon may lead to a misinterpretation of the supplied equivalents in bilingual dictionaries.
Thesis (MA. (Translation Studies and Linguistics)) -- University of Limpopo, 2012
Keywords: Bilingual dictionaries; Northern Sotho - English dictionaries; Northern Sotho language -- Dictionaries -- Polyglot; English language -- Dictionaries -- Polyglot; Lexicography